Mobile device-based Bluetooth Low Energy Database for range estimation in indoor environments - Pavel Pascacio; Joaquín Torres-Sospedra; Antonio R. Jiménez; Sven Casteleyn (Scientific Data, 2022)
Measurement(s) Received Signal Strength of Bluetooth Low Energy Technology Type(s) Bluetooth Low Energy Factor Type(s) position Sample Characteristic - Organism Mobile devices Sample Characteristic - Environment Indoor enviroments